Long‐Term Variations of Energetic Electrons Scattered by Signals From the North West Cape Transmitter - Jingle Hu; Zheng Xiang; Xin Ma; Yangxizi Liu; Junhu Dong; Deyu Guo; Binbin Ni (Space Weather)
Abstract Very‐low‐frequency (VLF) signals emitted from ground‐based transmitters for submarine communication can penetrate the ionosphere and leak into the magnetosphere, leading to electron precipitation via wave‐particle interaction and thereby providing a potential means for radiation belt remediation. In this study, we systematically analyze the dependence of quasi‐trapped electron fluxes scattered by signals from the North West Cape (NWC) transmitter on electron energy, L‐shell, and geomagnetic activity (i.e., the Dst index) using long‐term measurements from the DEMETER satellite. Considering potentially changed theoretical cyclotron resonant condition, we find that the variations of wave normal angle (WNA) of NWC transmitter signals or of the background electron density can explain the variated “wisp” positions in energy versus L plane. The long‐term data analyzation suggests that the energy‐dependences increases can help to distinguish the different source mechanisms of quasi‐trapped electrons. The enhancement of quasi‐trapped electron fluxes induced by NWC transmitter signals is more obvious at L = 1.8 than L = 1.6 due to higher trapped flux levels and strong pitch angle diffusion induced by transmitter signals.